Sosiologi Anomie di Era Digital: Studi Kualitatif atas Fenomena Catchphrase KaburAjaDulu - Nurfa’is, Fa’iza; Harianto, Sugeng (KOMUNITAS: Jurnal Ilmu Sosiologi, 2025)
The viral phenomenon of the #KaburAjaDulu catchphrase on social media during 2024–2025 reflects the emergence of anomie in digital society. This study aims to analyze the meaning of the catchphrase in digital interactions and interpret it through Durkheim’s theory of anomie and Merton’s strain adaptation. A qualitative approach was employed, using social media content analysis, in-depth interviews with 20 active users, and focus group discussions with students and young workers. The findings reveal that #KaburAjaDulu is not merely a humorous trend but a symbolic expression of escape from socio-economic pressures, as well as a creative form of criticism toward weak social systems. Two dominant patterns emerged: retreatism, representing symbolic withdrawal, and innovation, representing creative ways of criticizing social structures. Moreover, the catchphrase fosters digital solidarity, enabling young people to share collective emotional experiences online. This study concludes that Durkheim’s classical concept of anomie remains relevant in analyzing contemporary phenomena, while digital sociology perspectives are necessary to further capture the dynamics of modern society. (;).